2021
DOI: 10.3390/s21237772
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Estimating Tactile Sensation by Machine Learning Based on Vibration Information Obtained while Touching an Object

Abstract: The tactile sensation is an important indicator of the added value of a product, and it is thus important to be able to evaluate this sensation quantitatively. Sensory evaluation is generally used to quantitatively evaluate the tactile sensation of an object. However, statistical evaluation of the tactile sensation requires many participants and is, thus, time-consuming and costly. Therefore, tactile sensing technology, as opposed to sensory evaluation, is attracting attention. In establishing tactile sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…3. A tactile sensor equipped with strain gauges inside it [10] is mounted on a friction tester (TL201s, Trinity-Lab Inc., Japan). The tactile sensor consists of a two-layer silicone rubber pad with different hardness, and two strain gauges are attached to phosphor bronze plates in each layer.…”
Section: B Vibrations When Samples Are Traced By a Tactile Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…3. A tactile sensor equipped with strain gauges inside it [10] is mounted on a friction tester (TL201s, Trinity-Lab Inc., Japan). The tactile sensor consists of a two-layer silicone rubber pad with different hardness, and two strain gauges are attached to phosphor bronze plates in each layer.…”
Section: B Vibrations When Samples Are Traced By a Tactile Sensormentioning
confidence: 99%
“…To reproduce tactile sensations, technologies to quantify the tactile sensation of an object and to display tactile sensations using a tactile display are necessary. To quantify tactile sensation, it has been suggested that focusing on vibration information at the time of object touch is an effective approach given the human tactile perception mechanism [8], [9], [10], [11]. Tactile displays…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach is to extract meaningful information from vibration data obtained by tracing a simple vibration sensor on an object [16][17][18][19][20][21][22]. Because the four types of mechanoreceptors in our body have different frequency characteristics [23][24][25], they work as lters for vibration stimulations on the skin.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the meaningful information for humans is not the entire vibration data but is hidden in the vibration data. Previous research [16][17][18][19] focused on extracting meaningful information; we believe that it is quite promising because the information or feature quantities are often extracted based on the characteristics of human mechanoreceptors. By doing so, it becomes possible to interpret tactile sensation based on human perceptive characteristics.…”
Section: Introductionmentioning
confidence: 99%